PENGARUH EXPERIENTIAL MARKETING DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN HOTEL PUSAKO BUKITTINGGI - Dila Selfia; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted at Hotel Pusako Bukittinggi. Soekarno Hatta street, No. 7 Bukittinggi. Hotel Pusako Bukittinggi chosen as a test site for Pusako Bukittinggi has a significant problem that the room occupancy rate in the last 5 years not mencapapi targets set by the hotel. The purpose of this study was conducted to determine the influence of experiential marketing and brand image of the customer loyalty Pusako Bukittinggi.In this research methodology is descriptive and quantitative with SPSS, where samples were used that customers Pusako Bukittinggi. To determine the sample using the formula Slovin, sampling with accidental sampling method. The technique of collecting data through interviews, observation and questionnaires,From the results of this study shows experiential marketing variables have a positive influence on customer loyalty Pusako Hotel Bukittinggi. And the brand image variable partially has a positive influence on customer loyalty Pusako Hotel Bukittinggi. And then simultaneously experiential marketing and brand image have a positive effect on customer loyalty Pusako Hotel Bukittinggi. For further research it is advisable to add independent variables that can affect customer loyalty, such as customer satisfaction.Keywords: Experiential marketing, brand image and customer loyalitatas